Finite element analysis of components subjected to ratchetting and creep - Hardy, S.J. (1983)
Many components in conventional and nuclear power plant, chemical plant and aero engines may be subjected to severe loading conditions, i.e. loads which cause reverse plasticity and/or incremental growth (Ratchetting). If operating temperatures are high, creep strains may also be significant and may exacerbate the ratchetting process. Also the residual stress fields associated with the cycling of load in the plastic region for a material will influence the accumulation of strain during the dwell periods between cycles when steady loading is sustained.